A phenomenological study of mathematics academic anxiety and mathematics pedagogical anxiety in pre-service elementary school teachers - Pahmi, Samsul; Priatna, Nanang; Suhendra, Suhendra; Martadiputra, Bambang Avip Priatna; Muhaimin, Lukman Hakim (Universitas Islam Negeri Raden Intan Lampung, 2025)
This phenomenological study investigates mathematics academic anxiety and pedagogical anxiety among pre-service elementary school teachers. Data were collected through in-depth interviews, questionnaires, and observations involving pre-service teachers in teaching practice. The findings reveal that most participants experience high to very high levels of anxiety, both as mathematics learners and as future educators. Academic anxiety is more dominant, often manifesting as negative thoughts, overthinking, and avoidance behaviors, while pedagogical anxiety is slightly lower due to a greater sense of control during teaching practice. The sources of anxiety are multifaceted, including internal factors such as lack of confidence and negative past experiences, as well as external pressures from the educational environment. These results highlight the urgent need for systematic interventions in teacher education programs, such as anxiety management training, self-efficacy workshops, and supportive learning environments, better to prepare pre-service teachers for the challenges of mathematics instruction. Despite its contributions, the study is limited by its cross-sectional design and focus on a single institution. Future research should consider longitudinal approaches and broader samples. Addressing mathematics anxiety among pre-service teachers is crucial for developing confident and competent mathematics educators, ultimately improving the quality of mathematics learning in elementary schools.